Interbank Markets and Frictions - Mikael Reimer Jensen (Copenhagen Business School (CBS), 2016)
In the rst essay we look at the Danish interbank market and how it functioned during the nancial crisis. Prior to the nancial crisis the view seemed to be that the money markets were well functioning and capable of handling stress in nancial markets. This is the conclusion in Fur ne (2001, 2002) who analysis the US money market during the crisis in the autumn of 1998 where Russia e ectively defaulted on its sovereign debt. However, the recent nancial crisis was a lot more severe than the one in 1998. During the recent crisis we have seen the volatility of money market rates spike and many central banks have conducted unconventional monetary policies. Whether the interbank markets are robust is thus a relevant question again. A key element in our analysis is that the total amount of liquidity in the interbank market is constant when central bank interventions are absent. A negative shock to one bank's liquidity holdings should correspond with a positive shock for another bank's liquidity holding. In a market with no frictions, banks faced with liquidity shocks should be able to absorb these by borrowing from those with surplus liquidity.
hdl:10398/9385
Keywords: 650